ARALASH LIGANDLI Cr(III), Cu(II) VA Co(II) KOMPLEKS BIRIKMALARINING BIOKORROZIYAGA QARSHI FAOLLIGI - Ganiyev , Baxtiyor; Mardonov, O‘ktam (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
In this study, synthesized complex compounds were tested against biocorrosion of SRB (sulfate reducing bacteria) at enterprises for the production and storage of oil and petroleum products, and an analysis of the results is given.